Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Indojaya Agrinusa Deli Serdang - Abdi Hannan Nasution; Rukmini Rukmini (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to test and determine whether there is an effect of work discipline on employee performance at PT. Indojaya Agrinusa Deli Serdang. The population in this study were all employees of PT. Indojaya Agrinusa Deli Serdang as many as 220 employees. The sample was determined by simple random sampling technique, with 69 employees as respondents. Information collection methods used are primary data and secondary data. Analysis of the data used is simple linear regression analysis, correlation coefficient, t test (partially), and the coefficient of determination. Based on the results of the analysis of the significance test (t-test), work discipline is proven to have a positive and significant effect on employee performance as seen from the t-test where the t-count produced is 4.141 greater than the t-table 1.998 and the significance value is 0.000. Based on the empirical facts obtained, so that it can be stated that the research independent variable, namely Work Discipline, has a positive and significant influence on employee performance at PT. Indojaya Agrinusa Deli Serdang, the leadership needs to improve policies related to Work Discipline